The Implementation of Ultra Petita Principle in Decisions on Corruption Cases in Indonesia (A Study of Legal Sociology) - Rizka Wahyuni Amusroh; Haeranah; Hasbir Paserangi (LEGAL BRIEF, 2022)
This study aims to analyze the implementation of the ultra petita principle in criminal procedural law in Indonesia and to analyze the implementation of the ultra petita principle in decisions on corruption cases from the perspective of the theory of legal purposes. This research is a Sociology of Law research with Statue Approach, Conceptual Approach and Legal Sociology Approach. The material obtained is in the form of primary legal material and secondary legal material which is analyzed systematically and qualitatively in this case it will examine all data collected based on primary legal material and secondary legal material, which will then be connected with principles, legal theories, as well as the formulation of existing legislation so that a conclusion can be drawn in order to answer the problem studied. decision in corruption cases, especially related to the Juliari P. Batubara case, is justifiable because basically the judge decides according to the prosecutor's indictment, not the indictment. The judge has the authority to decide on a case based on the prosecutor's demands if it is in accordance with the legal facts at trial but must remain within the minimum maximum limit of the article suspected. In the decision on the criminal act of corruption, Juliari P. Batubara focused more on the aspect of legal certainty in the theory of legal purposes.